The effects of health status and child mortality on the African economies - Sirag, Abdalla; Faris, Arbab Ismail; Abdelmagid, Salah Abdelgadir; Mohamed Nor, Norashidah (Penerbit UKM, 2022)
The current study aims to examine the economic effects of health status. Employing data from 43 African countries, this study utilized the Pooled Mean Group estimation method of the Autoregressive Distributed Lag (ARDL) for cointegration to analyze the short-run and long-run relationship between health status and economic growth. In assessing the health status, we use life expectancy, infant mortality rates and mortality rate under the age of five measures. The results show that life expectancy in the long term was positively correlated with GDP per capita. In addition, infants and under-five mortality rates for both categories were negatively linked to the degree of long-term economic growth, suggesting a positive correlation between health status and growth. The study contributes to our understanding of the significance of health status as a main ingredient of economic growth in the African continent. Therefore, African policy makers are urged to pay particular attention to their healthcare services and any other factors that can help improve the health of their people.